New cross-layer reputation mechanism for mobile cloud computing - YU Mengyang, LIN Hui; TIAN Youliang (网络与信息安全学报, 2018)
Users are facing increasingly serious security threats such as data leakage and privacy exposure while using various mobile cloud services. Based on the data security and privacy protection for mobile cloud computing research background, combining the cross-layer design and credit mechanism, in the node between the introduction of the MAC layer and network layer in the process of credit evaluation of factors affecting user reputation, to identify and manage internal malicious nodes. The credibility of the simulation results show that the proposed mechanism can effectively resist the internal defamation and multilayer attack, enhance the credibility of mobile terminals, thus improve the mobile cloud service data security and privacy protection.